Association between the Level of Aspiration and Achievement of Students of Secondary Level - Poudel, Tek Narayan; Maharjan, Ram Krishna (Journal of Advanced Academic Research, 2018)
Aspiration levels play an important role in everyday decision making. In practice, however, decisions are not based on an aspiration level alone. The aspiration level and the overall probabilities of success and failure may receive special attention, but subjects will not be completely insensitive to difference within the classes of gains and losses. Aspirations have a significant impact on pupil attainment net of family background and other individual factors, but their effect is reduced when examining pupil progression. Some students, particularly from low-income or first-generation backgrounds, in spite of having high aspirations fail to meet their goals to attend college. Aspiration is a strong desire to achieve something in life. Every people they want to be successful man in life, they want famous, popular in society, so aspiration has vague meaning and sense. In this research student of Nepal they have high aspiration in life. Some of they want social worker, doctor, pilot engineer, great motivator and great leader in future. The study was conducted among the 511 students of grade ten students of three districts of Nepal.